Real-World Effectiveness of Single-Inhaler Triple Therapy for COPD: Impact of Diabetes Comorbidity - Sophia Eilat-Tsanani; Pierre Ernst; Samy Suissa (COPD)
Background Type 2 diabetes is a frequent comorbidity in chronic obstructive pulmonary disease (COPD) patients, with the GOLD treatment recommendations asserting that the presence of diabetes be disregarded in the choice of treatment.Methods In a cohort of COPD patients with frequent exacerbations, initiators of single-inhaler triple therapy or dual bronchodilators were compared on the incidence of COPD exacerbation and pneumonia over one year, adjusted by propensity score weighting and stratified by type 2 diabetes.Results The COPD cohort included 1,114 initiators of triple inhalers and 4,233 of dual bronchodilators (28% with type 2 diabetes). The adjusted hazard ratio (HR) of exacerbation with triple therapy was 1.04 (95% CI: 0.86–1.25) among COPD patients with type 2 diabetes and 0.74 (0.65–0.85) in those without. The incidence of severe pneumonia was elevated with triple therapy among patients with type 2 diabetes (HR 1.77; 1.14–2.75).Conclusion Triple therapy in COPD is effective among those without, but not those with, type 2 diabetes. Future therapeutic trials in COPD should consider diabetes comorbidity.